Double demands on the care of the aging patient during psychiatric hospitalization (Research, Society and Development, 2020)
The patient with mental disorder may experience an accelerated aging process when compared to the general population. Psychiatric hospitalization is a moment of disruption of mental function, which can contribute to the worsening of pre-existing clinical conditions, or even the emergence of comorbidities, increasing the complexity of the patient's condition. This study aimed to investigate the health care demands of aging patients with mental disorders. Quantitative approach, with temporal cut and use of simple descriptive statistics and measures of central tendency in data analysis. It was possible to prove, through the collected medical records, that almost half of the patients had clinical diagnosis and/or health problems related to physical problems. Considering the complexity of care towards aging patients with mental disorders, which can present comorbidities of physical nature, it is important to identify physical health problems early, as well as to prevent chronic non-communicable diseases, during and after hospitalization.